A γ-glutamylcysteine ligase AcGCL alleviates cadmium-inhibited fructooligosaccharides metabolism by modulating glutathione level in Allium cepa L. - Luo, Wei; Long, Yuming; Feng, Zili; Li, Rui; Huang, Xiaojia; Zhong, Jiaxin; Liu, Dongyun; Zhao, Hongbo (Journal of hazardous materials, 2021)
Fructooligosaccharides (FOS) are important carbohydrates in plants. Cadmium (Cd) toxicity limits growth and development in several plant species. Whether FOS metabolism is affected by Cd and the molecular mechanisms of tolerance of the effects of Cd toxicity in plants remain enigmatic. In the present study, FOS metabolism was analyzed under Cd stress in onion (Allium cepa L.). Results showed that Cd stress can inhibit FOS accumulation in onion, followed by the upregulation of a putative onion γ-glutamylcysteine ligase gene AcGCL. Heterologous expression of the AcGCL protein in Escherichia coli revealed that this recombinant enzyme has GCL activity. Furthermore, overexpressing AcGCL significantly increased glutathione (GSH) accumulation in young onion roots under Cd treatment, accompanied by increased phytochelatin (PC) amount, and increased transcript expression of GSH synthetase (GS), and phytochelatin synthase (PCS) genes. Notably, compared with control, overexpressing AcGCL ameliorated Cd phytotoxicity on onion FOS metabolism, which correlated with increased FOS synthesis. Taken together, these results suggest that the function of AcGCL as a γ-glutamylcysteine ligase can alleviate Cd inhibited FOS metabolism by modulating GSH levels in onion.
Gesehen am 04.11.2021